2015
DOI: 10.1021/acs.molpharmaceut.5b00113
|View full text |Cite
|
Sign up to set email alerts
|

A 17-mer Membrane-Active MSI-78 Derivative with Improved Selectivity toward Bacterial Cells

Abstract: Antimicrobial peptides are widely recognized as an excellent alternative to conventional antibiotics. MSI-78, a highly effective and broad spectrum AMP, is one of the most promising AMPs for clinical application. In this study, we have designed shorter derivatives of MSI-78 with the aim of improving selectivity while maintaining antimicrobial activity. Shorter 17-mer derivatives were created by truncating MSI-78 at the N-and/or C-termini, while spanning MSI-78 sequence. Despite the truncations made, we found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 48 publications
1
25
0
1
Order By: Relevance
“…Indeed, in the course of earlier clinical trials where patients were treated either with pexiganan cream or with active oral antibiotics, and compared with the placebo group, pexiganan’s performance proved it to be a possible alternative to oral antibiotics [ 51 ]. These findings triggered several research works focused on pexiganan and related peptides [ 52 , 53 , 54 ], and motivated the patenting of a 0.8% pexiganan acetate cream (Locilex ® , earlier known as Cytolex) in several countries, by the pharmaceutical company Dipexium Pharmaceuticals, Inc. (Houston, TX, USA) in 2016 [ 55 , 56 ]. However, Locilex ® failed approval by the competent international organizations, on the grounds that its efficacy was not proven superior to that of classic oral antibiotics in any of the clinical trials undertaken to date, which include a recent Phase 3 clinical trial promoted by Dipexium, now merged with PLx Pharma, Inc. (Houston, TX, USA) [ 57 ].…”
Section: Wound-healing Antimicrobial Peptidesmentioning
confidence: 99%
“…Indeed, in the course of earlier clinical trials where patients were treated either with pexiganan cream or with active oral antibiotics, and compared with the placebo group, pexiganan’s performance proved it to be a possible alternative to oral antibiotics [ 51 ]. These findings triggered several research works focused on pexiganan and related peptides [ 52 , 53 , 54 ], and motivated the patenting of a 0.8% pexiganan acetate cream (Locilex ® , earlier known as Cytolex) in several countries, by the pharmaceutical company Dipexium Pharmaceuticals, Inc. (Houston, TX, USA) in 2016 [ 55 , 56 ]. However, Locilex ® failed approval by the competent international organizations, on the grounds that its efficacy was not proven superior to that of classic oral antibiotics in any of the clinical trials undertaken to date, which include a recent Phase 3 clinical trial promoted by Dipexium, now merged with PLx Pharma, Inc. (Houston, TX, USA) [ 57 ].…”
Section: Wound-healing Antimicrobial Peptidesmentioning
confidence: 99%
“…However, these AMPs also have limitations for commercial and clinical applications such as weak activities, nonspecific cytotoxicity, and poor pharmacokinetic properties. For example, pexiganan (MSI-78) derived from magainin developed as a topical agent failed because it was not superior to other treatment methods [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Costa et al and Barbosa et al showed the importance of peptide attachment site in covalent immobilization on antimicrobial activity [14,15,22]. hLF (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and Dhvar-5 possess a head-to-tail amphipathicity that probably promotes distinctive interactions with bacteria. In this work, we showed that the antimicrobial activity of the α-helical MSI-78(4-20) peptide was not affected by attachment site upon immobilization onto chitosan films, probably due to the distribution of the hydrophobic and hydrophilic amino acids along the sequence.…”
Section: Discussionmentioning
confidence: 99%